DISTRIBUSI KATA SAPAAN AREK DAN BOCAH DI PERBATASAN KABUPATEN MALANG DAN BLITAR - Mardiana, Dwi Ira Ningrum Ana; NURHAYANI, IKA; HAMAMAH, HAMAMAH (University of Brawijaya, 2022)
This article aims to describe the distribution use of the greeting â€œarekâ€ and â€œbocahâ€ in the border area of Malang and Blitar Regency. The researchers di three research steps: observation, interview, and introspection. The data of this article are variations of Javanese in the border area of Malang and Blitar Regency, while the data sources are people who live in the border area. There are six research points are Arjosari, Ngreco, Karangkates, Jugo, Kalirejo, and Ngadri. The results of this article are the use of greeting â€œbocahâ€ which is commonly spoken in Blitar Regency, also spoken by the people in Malang, whose area is adjacent to Blitar Regency. This proves that the dialects of Javanese in Blitar are more potent than the Malang Regency.